Histomorphometrical Study on Regional Variation in Distribution of Sweat Glands in Buffalo Skin - Debajit Debbarma; Varinder Uppal; Neelam Bansal; Anuradha Gupta (Dermatology Research and Practice)
The study was conducted on skin of 24 buffaloes collected from slaughter house. The skin tissues were collected from dorsal, lateral, and ventral parts of head, neck, thorax, abdomen, and tail regions and fixed in 10% neutral buffered formalin. The tissues were processed for paraffin blocks preparation by acetone benzene schedule. The paraffin sections of 5-6 μm were cut with rotary microtome and stained with hematoxylin and eosin. The sweat glands in buffaloes were of saccular and simple coiled tubular type. Most of the sweat glands were associated with hair follicles and consisted of a coiled secretory portion (body) and a straight duct. The secretory portion was made up of glandular tubules, myoepithelium, and basement membrane. The duct portion had a narrow lumen and was lined by simple cuboidal epithelium. The glandular epithelium was simple squamous, simple cuboidal, or low columnar type depending upon their stage of secretary activity. Two types of sweat glands were observed, i.e., apocrine and merocrine. Large number of blood vessels and nerve fibers were observed in the vicinity of the sweat glands. In head, neck, and tail regions the maximum number of sweat glands/mm2 was observed in dorsal side which did not vary significantly (p<0.05) from lateral and ventral side. In abdomen region the number of sweat glands/mm2 was maximum on lateral region which varied significantly from ventral region (p<0.05). Overall, the maximum number of sweat glands/mm2 was in head region followed by abdomen, thorax, neck, and tail but without any significant (p<0.05) difference. Maximum sweat gland diameter was found in abdomen region followed by thorax, head, neck, and tail region.